10.1016/s1558-0164(12)70092-5 (CrossRef Listing of Deleted DOIs, 2000)
Multiple palatal graft harvesting techniques are available for clinicians providing root coverage and gingival augmentation procedures. However, existing research does not establish the risk of epithelial inclusion-related sequelae for each graft type. Hypothetically, use of a de-epithelialized gingival graft (DGG) may both increase the burden of seeded epithelial cells and heighten the risk of a rare late complication. A male patient aged 44 years presented with a firm, painless, ovoid nodule (approximately 12 × 9 × 3 mm) in the alveolar mucosa overlying the maxillary right canine. The patient reported receiving a root coverage procedure in the maxillary right quadrant approximately 9 months prior, and the implanted graft was confirmed to be a DGG. The patient elected an excisional biopsy to remove the lesion. The nodule was removed through a single vertical incision, and histologic assessment confirmed the diagnosis of epithelial inclusion cyst. Eight weeks following the biopsy, no gingival recession was noted at the canine. However, some scarring was observed in the alveolar mucosa. Limited evidence suggests complete elimination of epithelial cells from palatal grafts is rarely, if ever, attainable. Additional clinical investigation is needed to determine whether DGGs pose increased risk of inclusion-related complications. During the informed consent process, clinicians should advise patients of the small risk of inclusion-related complications and the limitations in available evidence. Compared with alternative autogenous graft types, de-epithelialized gingival grafts (DGGs) are associated with reduced inclusion of adipose and glandular tissue, superior clinical handling, and enhanced augmentation of tissue thickness. Complete removal of epithelial cells prior to DGG implantation appears unattainable. Intuitively, use of a DGG may increase the risk of epithelial inclusion cyst formation, although existing research is inadequate. When treating gingival recession (exposed tooth root surfaces), various techniques for obtaining soft tissue from the roof of the mouth are available for dental surgeons. One problem associated with use of tissue from the roof of the mouth in surgical procedures is that epithelial cells can become trapped beneath the gum tissue. The trapped epithelial cells may lead to cyst formation or presence of a pasty white or yellowish material months after the procedure. Compared with alternative methods, one of the techniques (the de-epithelialized palatal graft) may be more likely to produce problems related to trapped epithelial cells. However, the research necessary to establish this increased risk has not been conducted. This report presents a case of cyst formation in a patient who had previously received a de-epithelialized palatal graft.